Epidemiological survey of oral lesions in children and adolescents in a Brazilian population. Issue 11 (November 2015) - Pessôa, Camila Porto; Alves, Técia Daltro Borges; Santos, Nilton César Nogueira dos; Santos, Heloísa Laís Rosário dos; Azevedo, Alana de Cássia Silva; Santos, Jean Nunes dos; Oliveira, Márcio Campos
Abstract Objectives To identify the most frequent oral lesions in children and adolescents in Reference Units of Oral Lesions of Public Universities of Bahia, Brazil, in the period between 1996 and 2010, and estimate the association between socio-demographic factors and type of oral lesions found. Methods Cross-sectional study using secondary data obtained from medical records, records of requests and reports of biopsies from patients aged between 0 and 19 years treated in Reference Units of Oral Lesions of Public Universities in Bahia, Brazil, in the period between 1996 and 2010. For data analysis, we used descriptive analysis of the variables, bivariate analysis by calculating the prevalence ratios (PR) to assess the association between oral lesions and gender, age and skin color, and the analysis of potential modifying and confounding effects by logistic regression modeling. To calculate the p-value of associations, we used the chi-square test, and p < 0.05 was considered statistically significant. Results There were 360 records of patients between 0 and 19 years (8.7% of total records). The results revealed 72 different types of lesions. The most prevalent lesions were mucoceles (14.2%), fibroma (5.6%) and pyogenic granuloma (5.3%). The variable "age" was the only socio-demographic characteristics among those analyzed that showed a statistically significant association with both neoplastic and non-neoplastic lesions, according to bivariate analysis, considering the rates adjusted for potential confounders. Neoplastic lesions appeared more often in the age group 0–9 years, while the non-neoplastic lesions were more prevalent in individuals 10–19 years. There was no effect modification noted in the predictive models analyzed. Conclusions The study identified the existence of a broad range of oral lesions affecting children and adolescents. Most of the lesions found were of the non-neoplastic type. The age of individuals was associated with the type of oral lesion found.